ENoLL - European Network of Living Labs (European Network of Living Labs)
The European Network of Living Labs (ENoLL) is an international non-profit association which aims to promote and enhance user-driven innovation ecosystems,more precise the Living Labs concept globally.ENoLL focuses on facilitating knowledge exchange, joint actions and project partnerships among its historically labelled +475 members, influencing EU policies, promoting living labs and enabling their implementation worldwide.
Carte d'information Type d’organisme : Organisation internationale à but non lucratif / Réseau de laboratoires vivants / Living Labs network Échelle géographique : Europe Type de contenu et outils proposés - Programmes de renforcement des capacités - Processus de labellisation de haut niveau - Certifications de laboratoires vivants - Groupes de travail orientés vers l'action - Matériel de connaissances : boîte à outils, webinaires, podcasts, ouvrages, cours en ligne - Nouvelles et évènements Public visé : Organisations ayant des activités et des intérêts dans l'innovation ouverte axée sur les utilisateurs.
Keywords: Europe; Organisme de soutien